Service Quality in Maja Baru Village, Maja, Lebak Regency - Wulansari, Ratu Diah; Setiabudi, Tardi; Aziz, Anggi Fauzan (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
The problems behind the researchers in conducting this study include the effectiveness of services still not achieving the desired results, lack of discipline of sub-district employees in attendance when entering and leaving the office, and lack of response of service officers to the community who want to perform services. This study was conducted to determine how and to what extent the quality of service in Maja Baru Village, Maja District, Lebak Regency. The method used in this research is qualitative research, namely to understand the phenomena experienced by research subjects holistically in a descriptive way in the form of words and language. Researchers use in-depth interviews, documentation and observations in data collection. Research informants are determined by Purposive Sampling, where researchers determine for themselves who are research informants. The research instrument is based on Service Quality from the theory of Zeithaml where there are 5 (five) dimensions of quality, namely Tangibles, Reliability, Responsiveness, Assurance, and empathy. Data processing and analysis techniques use qualitative data analysis techniques that are carried out from the first data until the research ends by following the concepts of Miles and Huberman. The results of the research analysis of service quality in Maja Baru Village, Maja District, Lebak Regency in its implementation have been good, although the limitations and level of Service Quality in Maja Baru Village, Maja District, Lebak Regency are still not optimal.